Intraspecific phylogenetic analysis of rice leaf folder, Cnaphalocrocis medinalisGuenee (Lepidoptera: Crambidae) populations across five agro-ecological units in Kerala - SUBHAGAN, SEENA R; PATHROSE, BERIN; CHELLAPPAN, MANI; NAIR, SMITA; D, DHALIN (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2023–2024 at College of Agriculture, Vellanikkara, Kerala to investigate the intraspecific molecular phylogeny by utilizing mtCO1 gene sequences of the rice leaf folder, Cnaphalocrocis medinalis Guenee (Lepidoptera: Crambidae), across five major rice (Oryza sativa) growing agroecological units (AEUs), viz. AEU 3- Onattukara Sandy plains, AEU 4-Kuttanad, AEU 6-Kole lands Thrissur, AEU 20-Wayanad Central Plateau and AEU 23-Palakkad Eastern Plains in Kerala. While all populations clustered within the same clade, medinalis from Onattukara exhibited separate branching, albeit sharing similarities with Kuttanad populations. In contrast, populations from Thrissur and Wayanad displayed a closer resemblance, while those from Palakkad exhibited similarities with populations from China and Jharkhand in India. Moreover, the observed genetic structuring suggested regional differences in population dynamics, with populations from Southern Kerala (Onattukara and Kuttanad) exhibiting closer genetic grouping compared to those from Northern Kerala (Wayanad, Palakkad, and Thrissur). Analysis of percent identity matrices unveiled a high level of genetic similarity among C. medinalis populations across Kerala's AEUs, ranging from 98–99%. Notably, Kuttanad populations shared 99.85% of their identity with those from Onattukara and Wayanad, while Wayanad populations shared the same level of identity as Thrissur. Despite the regional differences, our study did not observe an apparent "barcode gap" typical of COI sequences. These findings shed light on the possibility of seasonal migration patterns, inbreeding events, and the subsequent distribution dynamics of the rice leaf folder across Kerala. Moreover, the potential impact of migration on disseminating resistant alleles among insect populations is a critical issue that warrants comprehensive investigation.